Developments toward ferrofluidic space technology as part of the technology demonstrator mission FINIX - Mächtig, L.; Schwerdhelm, M.; Ferrer Garcia, M.; Ben Rajiba, Y.; Kob, M.; Eisenbach, M.; Friedrich, T.; Al Rifai, Y.; Heuser, P.; Dietrich, J.; Heinz, N.; Bölke, D.; et al. (CEAS space journal, 2025)
The Small Satellite Student Society at the University of Stuttgart (KSat e.V.) has a strong history of ferrofluid-based research, demonstrated through ISS projects PAPELL and FARGO, as well as the REXUS sounding rocket project FerrAS. The latest endeavor, project FINIX, is scheduled to launch on the REXUS 34 sounding rocket in Q1 2025. Building on these previously conducted missions, FINIX seeks to advance ferrofluid-based solutions with future applications in space systems. These novel developments hold the potential to replace conventional mechanical components in space applications, which are subject to wear and tear and hence represent a limiting factor for space missions. This paper details the experiments planned for the technology demonstrator mission FINIX, focusing on the development of an electrical switch and a pump, and their connection to earlier developments. The design, testing, and validation processes of these ferrofluid-based experiments will be discussed, highlighting the scientific objectives and innovations of the project.